Preparation of CuO Nanoparticles for Improving Base Oil Properties - Al-Tabbakh, Ban A.; Jaed, Dalya M.; Qubian, Nawar A; Kareem, Sura (Journal of Petroleum Research and Studies, 2022)
Abstract Through this research, copper oxide nanoparticles were prepared via precipitation method using copper nitrate as a starting material. The resulting nanomaterial characteristics were diagnosed using available technologies such as AFM, XRD, B.E.T. surface area, pore-volume, pore size, and FTIR. For modern industries, lubricants are efficient materials for reducing friction between moving surfaces. CuO nanoparticles are used as an additive that is dispersed in an oil phase. Ultrasound technique was used to disperse the nanomaterial in Stocks 60 base oil, and the effect of the ratios of the added nanomaterial on the final properties of the oil was studied. A ratio of 0.5, 1, 1.5, and 2% was used and mixed with an approbate amount of oleic acid and was dispersed using ultrasound. The prepared copper oxide nanoparticles had an average particle size of 31.76nm and crystallinity of 93.63%. The surface area was around 27.61 m2 / g. Diagnostic tests were carried out on the oil, as it led to an increase in the viscosity index gave high stability and good dispersion of the nanomaterial for a long time, as the viscosity index was re-examined during successive periods. The final characterization of the oil shows a good improvement in the viscosity index of 110 and the flashpoint increased to 240 ° C. By increasing the viscosity index leading to ease movement inside the tools and contact surfaces oil will overcome the severe conditions during operations.